2012
DOI: 10.1371/journal.pone.0052541
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Aorta and Protective Effects of Grape Seed Procyanidin B2 in db/db Mice Reveal a Critical Role of Milk Fat Globule Epidermal Growth Factor-8 in Diabetic Arterial Damage

Abstract: BackgroundAtherosclerosis is one of the major complications of type 2 diabetic patients (T2DM), leading to morbidity and mortality. Grape seed procyanidin B2 (GSPB2) has demonstrated protective effect against atherosclerosis, which is believed to be, at least in part, a result of its antioxidative effects. The aim of this study is to identify the target protein of GSPB2 responsible for the protective effect against atherosclerosis in patients with DM.Methods and ResultsGSPB2 (30 mg/kg body weight/day) were adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 48 publications
3
31
0
Order By: Relevance
“…The gene for MFGE8 is in a region linked with susceptibility to obesity and eating behaviors in humans (37,38). Additionally, circulating Mfge8 concentrations correlate with the degree of hemoglobin glycosylation and are elevated in diabetics, a disease with markedly increased prevalence in obese subjects (39,40). The work presented here identifies Mfge8 and the αvβ3 and αvβ5 integrins as a key pathway regulating enterocyte processing of dietary fats.…”
Section: Discussionmentioning
confidence: 81%
“…The gene for MFGE8 is in a region linked with susceptibility to obesity and eating behaviors in humans (37,38). Additionally, circulating Mfge8 concentrations correlate with the degree of hemoglobin glycosylation and are elevated in diabetics, a disease with markedly increased prevalence in obese subjects (39,40). The work presented here identifies Mfge8 and the αvβ3 and αvβ5 integrins as a key pathway regulating enterocyte processing of dietary fats.…”
Section: Discussionmentioning
confidence: 81%
“…In mouse models of obesity, Mfge8 expression is markedly induced in white adipose tissue after weight gain 21 . Further, circulating Mfge8 concentrations are elevated in patients with diabetes 22,23 and correlate with the extent of hemoglobin glycosylation 23 .…”
mentioning
confidence: 98%
“…Our previous studies showed that GSPB2 has protective effects against early stage endothelial dysfunction in DM [25]. Treatment of HUVEC with GSPB2 significantly inhibited the cell apoptosis induced by AGEs [18].…”
Section: Discussionmentioning
confidence: 93%